Recent Advances in the Genetics of Fractures in Osteoporosis - Koromani, Fjorda; Trajanoska, Katerina; Rivadeneira, Fernando; Oei, Ling (Frontiers in Endocrinology, 2019)
Genetic susceptibility, together with old age, female sex and low bone mineral density (BMD) are amongst the strongest determinants of fracture risk. The most recent large-scale genome-wide association study (GWAS) meta-analysis has yielded fifteen loci. This review focuses on the advances in the research of genetic determinants of fracture risk. We first discuss the genetic architecture of fracture risk, touching upon different methods and overall findings. We then discuss in a second paragraph the most recent advances in the field and focus covering the genetics of fracture risk and also of other endophenotypes closely related to fracture risk such as bone mineral density (BMD). Application of state-of-the-art methodology such as Mendelian randomization in fracture GWAS are reviewed. The final part of this review touches upon potential future directions in genetic research of osteoporotic fractures.